9(6c-1)-18=52c+9

Simple and best practice solution for 9(6c-1)-18=52c+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(6c-1)-18=52c+9 equation:


Simplifying
9(6c + -1) + -18 = 52c + 9

Reorder the terms:
9(-1 + 6c) + -18 = 52c + 9
(-1 * 9 + 6c * 9) + -18 = 52c + 9
(-9 + 54c) + -18 = 52c + 9

Reorder the terms:
-9 + -18 + 54c = 52c + 9

Combine like terms: -9 + -18 = -27
-27 + 54c = 52c + 9

Reorder the terms:
-27 + 54c = 9 + 52c

Solving
-27 + 54c = 9 + 52c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-52c' to each side of the equation.
-27 + 54c + -52c = 9 + 52c + -52c

Combine like terms: 54c + -52c = 2c
-27 + 2c = 9 + 52c + -52c

Combine like terms: 52c + -52c = 0
-27 + 2c = 9 + 0
-27 + 2c = 9

Add '27' to each side of the equation.
-27 + 27 + 2c = 9 + 27

Combine like terms: -27 + 27 = 0
0 + 2c = 9 + 27
2c = 9 + 27

Combine like terms: 9 + 27 = 36
2c = 36

Divide each side by '2'.
c = 18

Simplifying
c = 18

See similar equations:

| 3750=3000c-900 | | 1.05(8000-y)+1.10y=8500 | | 1.05(8500-y)+1.10y=8500 | | 1.05(8500-y)+1.10=8500 | | p^2=27-6p | | 2(t-2)+3(2t+2)=-5(2-t) | | -2-5x=5+4x | | -2+5x=5+4x | | -3(-5)-3y=-6 | | 6y-0.8=7y | | 2+5x=5-4x | | 9(x-6)=8x-1 | | 8x-7=9x-6 | | -9(z-1)=-8z-4 | | 15+16x= | | 28+3y=28 | | .91(8000-y)+.97y=7800 | | 15x+16=x | | n*2-23=0 | | -l-19l-1-23-2= | | -19l-l-23-2= | | 5y^2-16+11=0 | | -4(-6)+y=29 | | -91=9t+8 | | 7x^3-x^2-112x+16=0 | | x+(x*.15)=27.6 | | 5(8c-1)-12=38c+5 | | .50(10x-2)=4 | | 34-52(12n-34)+235=32+101(35n-1) | | x^3+2x=110 | | 26a+26b= | | 15s^2+32s-7=0 |

Equations solver categories